2020
DOI: 10.4236/abb.2020.118028
|View full text |Cite
|
Sign up to set email alerts
|

The Bioprocessing Quick Wins from Avocado Fruit in Uganda

Abstract: Bioprocessing can help redeem the economic value for avocado (Persea americana) in Uganda. This study reviews the virgin potential of avocado bioprocessing in Uganda. Avocado consists of flesh, seed, and peel. The review indicates that the waste seed and peel are vital for development of high-value products. Both the edible part and waste (peel and seed) can be used for biogas production through a solid-state fermentation process. Biodiesel can be developed using avocado seed oil through a process called trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, their production limitations and the depletion of these fossil sources cause their price to increase on a regular basis [90]. Considering the significant amount of waste obtained by the avocado industry, the production of bioenergy and biofuels from these are regarded as possible alternatives to fossil fuels in the short-term [91].…”
Section: Biofuels and Bioenergymentioning
confidence: 99%
See 1 more Smart Citation
“…However, their production limitations and the depletion of these fossil sources cause their price to increase on a regular basis [90]. Considering the significant amount of waste obtained by the avocado industry, the production of bioenergy and biofuels from these are regarded as possible alternatives to fossil fuels in the short-term [91].…”
Section: Biofuels and Bioenergymentioning
confidence: 99%
“…To date, some studies have declared it possible to obtain biodiesel from avocado seed through transesterification, which simplifies the process due to the low content of free fatty acids and the presence of triglycerides [81,91,100]. Colombo et al determined that the fruit wastes have the potential to be transformed into biofuel.…”
Section: Biofuels and Bioenergymentioning
confidence: 99%
“…On the other hand, Reints et al [23] indicate that efforts should be made in the adoption of technologies related to efficient water management in avocado cultivation. Likewise, Baidhe et al [24] draw attention to the need to investigate opportunities for the processing of by-products products to strengthen the industrial development capacities of this crop. In this sense, Ramírez-Gil et al [14] found a relationship between the technological level (TL) of the production systems and the incidence of diseases in avocado agricultural systems in the neotropics.…”
Section: Introductionmentioning
confidence: 99%